A response to Letter to the Editor titled: Valproic acid for myoclonic epilepsy in POLG1 carriers can be fatal - Tarka, Sylwia (Folia Neuropathologica, 2021)
Dear Dr. Josef Finsterer, Thank you for your careful and thorough reading of our article and for the valuable comments. We agree that valproic acid is harmful in the mitochondrial disease and we want to add that the described case is currently being prosecuted as medical malpractice.